Design of Material Handling Equipment in the Bending Process Using KarakuriKaizen Method: An Analysis of Working Posture - Imansuri, Febriza Imansuri; Soekarno, Rahadyan Jyestha Soekarno; Prajoti, Harzya Dahmar Prajoti; Syarifudin, Ahmad Syarifudin; Violeta, Kesya Anatama Violeta; Wulansari, Isma Wulansari; Sumasto, Fredy Sumasto (JURNAL TEKNIK INDUSTRI, 2024)
This research discusses the analysis of work posture in the MMH activity of lifting products from thebending workstation to the Quality Control (QC) and packaging workstation. Observations weremade on the operator's working posture at the bending workstation in Kobar, Ltd, which producesrear brake components. The problems found were manual material handling activities in the form ofrepetitive lifting and placing products from the bending workstation to the QC and packagingworkstation. Work posture analysis was done using the Nordic body map questionnaire, REBA, andOWAS methods. Based on the results of the NBM questionnaire, fatigue occurred in the right elbow,left elbow, upper back, lower back, lower wrist, right wrist, and left wrist.Meanwhile, the results of the REBA method obtained a score between 4-7, which means that MMHactivities have a moderate risk and immediate improvement. Apart from that, based on the OWASmethod, a score of between 2-3 is obtained, so improvements must be made as soon as possible. Theimprovements made were by designing material handling tools using the principles of kaizenkarakuri and anthropometric ergonomics. This improvement eliminates the element of manualmaterial handling work and changes the position of the layout.